Small‐diameter artery decellularization: Effects of anionic detergent concentration and treatment duration on porcine internal thoracic arteries. Issue 4 (2nd December 2021) - Kostelnik, Colton; Hohn, Julia; Escoto‐Diaz, Carlos E.; Kooistra, Jesse B.; Stern, Matthew; Swinton, Derrick E.; Richardson, William; Carver, Wayne; Eberth, John
Abstract: Engineered replacement materials have tremendous potential for vascular applications where over 400, 000 damaged and diseased blood vessels are replaced annually in the United States alone. Unlike large diameter blood vessels, which are effectively replaced by synthetic materials, prosthetic small‐diameter vessels are prone to early failure, restenosis, and reintervention surgery. We investigated the differential response of varying 0%–6% sodium dodecyl sulfate and sodium deoxycholate anionic detergent concentrations after 24 and 72 h in the presence of DNase using biochemical, histological, and biaxial mechanical analyses to optimize the decellularization process for xenogeneic vascular tissue sources, specifically the porcine internal thoracic artery (ITA). Detergent concentrations greater than 1% were successful at removing cytoplasmic and cell surface proteins but not DNA content after 24 h. A progressive increase in porosity and decrease in glycosaminoglycan (GAG) content was observed with detergent concentration. Augmented porosity was likely due to the removal of both cells and GAGs and could influence recellularization strategies. The treatment duration on the other hand, significantly improved decellularization by reducing DNA content to trace amounts after 72 h. Prolonged treatment times reduced laminin content and influenced the vessel's mechanical behavior in terms of altered circumferential stress and stretch while further increasing porosity. Collectively, DNase with 1% detergent for 72 h provided an effective and efficient decellularization strategy to be employed in the preparation of porcine ITAs as bypass graft scaffolding materials with minor biomechanical and histological penalties.